STUDENTS READINESS FOR ONLINE LEARNING: CASE STUDY ON COMMERCE DEPARTMENT’S STUDENTS POLITEKNIK KUCHING SARAWAK - Hartyni Mastor; Hasimah Salleh; Khatijah Ibrahim, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The Covid-19 pandemic has had a profound effect on the country's education system. Regardless of the administrator and the teaching staff, the students are also affected by this situation. The Ministry of Higher Education has decided that the Online Teaching and Learning method (Pengajaran dan Pembelajaran Dalam Talian, PdPDT) will be implemented at the Polytechnic level, especially for the June 2020 session. The main purpose of this study is to identify the level of readiness and motivation of students of the Commerce Department Polytechnic Kuching Sarawak on the implementation of PdPDT. The study also examined the relationship between motivation and the level of readiness of students to follow online learning. Quantitative data is collected through a questionnaire distributed online to all active students of the Commerce Department who will attend lectures in the June 2020 session (excluding students who are undergoing Industrial Training and semester 1 students intake June 2020). A pilot study conducted found that the Cronbach’s alpha value was 0.970 and it showed a high level of reliability for the items tested. The scope of this study leads to the level of readiness and level of motivation of students only. The data obtained were analyzed using Statistical Package for Social Science (SPSS) version 20. Overall, the level of readiness (mean score: 3.40) and level of motivation (mean score: 3.32) of students of the Commerce Department on the implementation of online learning is at a moderate level. Respondents responded positively to PdPDT in assisting the new normal teaching and learning process.